Fintech Peer To Peer Lending Sharia as an Alternative Capital for MSME in Sidoarjo : Fintech Peer To Peer Lending Berbasis Syariah Sebagai Alternatif Permodalan UMKM Sidoarjo - Latifah, Fitri Nur; Ardiani, Ninda; Ariyanti , Novia; Syafitri , Mega Novita (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to explore the role of Islamic peer-to-peer lending fintech as an alternative solution to Sidarjo's MSME capital problem. As we know there are still many MSMEs still unbankable. So when capital issues arise, they are in trouble. Therefore, the existence of Sharia Fintech with P2P system is expected to be the solution to these problems. The study uses a qualitative case study method that collects secondary and primary data through interviews with Sidoarjo economic officials. The conclusion of this study shows that sharia peer-to-peer loan financing to MSME can improve his MSME's performance. Sidoarjo's MSMEs just lack understanding of Sharia Fintech P2P as an alternative to capital. Highlights: Sharia Fintech P2P as a solution for MSME capital problem Qualitative case study using secondary and primary data Lack of understanding hindering MSMEs from accessing Sharia P2P finance. Keywords: Islamic peer-to-peer lending,Fintech,MSMEs,Sidoarjo,Sharia finance